2020
DOI: 10.1186/s12948-020-00129-2
|View full text |Cite
|
Sign up to set email alerts
|

A gendered magnifying glass on COVID-19

Abstract: COVID-19 pandemia is affecting Countries worldwide with a gendered death excess as being a male represents, especially in the 50–69 years age group, an unfavourable factor. Females are constitutionally prone to defend themselves against pathogens with a stronger efficiency than males. As a fact, several genes involved into the regulation of the innate and adaptive immune response are strategically placed on the X-chromosome and, among them, pathogen-related receptors (PRRs), such as Toll-like receptor 7, suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 84 publications
1
27
0
2
Order By: Relevance
“…The systematic review and meta-analysis from Galbadage et al [ 12 ] showed that men are more likely to die from COVID-19 than women. Although a clear explanation of this association has not been established yet, it has been suggested that some biological and immunological pathways can play an essential role in the differential behavior of COVID-19 [ 13 ]. Some socio-behavioral and cultural aspects can also explain the more unfavorable scenario for men [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review and meta-analysis from Galbadage et al [ 12 ] showed that men are more likely to die from COVID-19 than women. Although a clear explanation of this association has not been established yet, it has been suggested that some biological and immunological pathways can play an essential role in the differential behavior of COVID-19 [ 13 ]. Some socio-behavioral and cultural aspects can also explain the more unfavorable scenario for men [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with disease occurrence, approximately similar distribution is detected among males and females at different age groups according to the WHO case-based surveillance system as of April 18, 2020[ 32 ]. However, from data on today in COVID-19, not only the progression of disease severity, but also mortality and fatality rates necessity to be clarified by age and, in addition by sex[ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…XCI is recognized during embryonic development and regularly preserved throughout the life[ 61 , 62 ]. However, a part of X-codified genes (almost 15%-23%) can discharge, fully or partly, from XCI and this privilege is suitable for those genes located in the pseudoautosomal regions (PAR) 1 and 2[ 32 , 63 ]. The ACE2 gene is located within PAR1 and the influence may not inevitably be an increased expression of ACE2 in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent case-series has shown that four young males with severe COVID-19 harbored rare TLR7 variants, which hampered interferon responses upon TLR7 engagement (60). Since TLR7 is located on the X-chromosome and is expressed bi-allelically, it has been suggested as one of the reasons for the sex bias, albeit in opposite direction, seen in AD and COVID-19 (61). These claims are yet to be proved, but it is becoming more apparent that a coordinated immune response is key for successfully controlling SARS-CoV-2 infection (62).…”
Section: Autoimmunity-associated Genes Providing Potential Insights Imentioning
confidence: 99%